Urban design practice : an international review ([S.l.] : RIBA Publishing, 2012)
Urban Design Practice gives a fascinating account of the state of urban design practice across the world today. Packed with invaluable local knowledge from on-the-spot contributors, its global scope offers an armoury of background facts and figures to professionals interested in exporting their skills internationally. Along the way it reveals how urban design is practiced, identifies a multitude of key concerns and refines our understanding of what urban design (so often a nebulous concept) means. Aimed broadly at practitioners masterplanners, architects, landscape architects, planners, civil engineers and students and academics of these disciplines, twenty chapters analyse a different country's urban design context. Fully illustrated and structured in a similar way, each chapter features a case study, general background economic statistics, and a handy 'quick guide' to the types of work available, the underlying legislation and tips for securing work. Features chapters of the following countries: Argentina, Australia, Brazil, China, the Czech Republic, Dubai, Egypt, England, France, Germany, India, Italy, Morocco, Netherlands, New Zealand, South Africa, Spain, Sweden and the USA.
Keywords: City planning